Empowerment of Papuan Women for Noken Knitted Product Diversification and Marketing Management - Muhammad Agus Sulaiman; I Ketut Atmaja Johny Artha; Yatim Riyanto (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2022)
This empowerment program aims to foster indigenous Papuan women to be empowered and more motivated in the creativity of diversifying Noken knitted products so that they are not always in the form of traditional bags. This research was conducted for nine months (March-November 2021) in the city of Jayapura. From the results of the study with a sample of 30 people, it was found that perceptions about the diversification of noken knitted products and with marketing management were denoted by (X) can foster the spirit of creativity in women's empowerment denoted by (Y) with t count showing 3.100 with a df value of 30-2 = 28, so the number df is 28 and the t table shows 1.701 with a significance value of = 0.05 (α = 5 percent) then it is stated that there is a correlation of variable (X) to variable (Y) so that it can be stated that H0 is rejected and H1 is accepted, because t count t table, it is stated that there is a correlation between the two variables. That the existence of product diversification and knowledge of marketing management will tend to increase women's empowerment and be motivated in improving the economy of indigenous Papuan women in diversifying noken knitting as well as gaining marketing management knowledge.